Analisis Risiko Keberlanjutan Pada Perusahaan Pertambangan Di Kalimantan Selatan Dengan Pendekatan Green Human Resource - Eka Santi Agustina (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This study aims to analyze sustainability risks in mining companies in South Kalimantan and examine the role of Green Human Resource Management (GHRM) in mitigating those risks. The research adopts a quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) with survey data collected from employees of several mining companies in South Kalimantan. The findings reveal that mining companies face sustainability risks in three key aspects: environmental, social, and governance (ESG). The implementation of GHRM practices shows varying levels, with green training and green performance appraisal being relatively well adopted, while green recruitment and green rewards remain less developed. The SEM-PLS results indicate that GHRM has a significant effect on sustainability risk mitigation with an R² value of 0.62, meaning that 62% of sustainability risk variations can be explained by GHRM practices. Among the GHRM dimensions, green training (β = 0.42, p < 0.001) is identified as the most dominant factor in reducing sustainability risks, followed by green performance appraisal (β = 0.31, p = 0.001) and green rewards (β = 0.18, p = 0.041). Conversely, green recruitment does not show a significant effect (β = 0.12, p = 0.227). These results highlight that strengthening internal capacity through green training and performance appraisal is more effective in mitigating sustainability risks than relying on green recruitment practices. The study contributes to the literature by linking GHRM to sustainability risk mitigation in the mining sector and provides practical implications for managers to enhance environmental and social responsibility through HRM practices